Pica Is Associated With Smoking and Self-Reported Stress Among Palestinian Pregnant Women: Cross-Sectional Study. (7th June 2021) - Zidan, Souzan; Badrasawi, Manal; Hamdan, May
Abstract: Objectives: 1. To determine the prevalence of pica among Palestinian pregnant women. 2. To identify substance most commonly ingested by Palestinian pregnant women. 3. To explore whether dietary habits and lifestyle factors are associated with pica practice among Palestinian pregnant women. Methods: A cross-sectional study was conducted among 170 pregnant women. Interview pre-tested structured questionnaire was administrated to pregnant women who were attending private gynecological clinics in Hebron district. Cronbach Alpha was used to determine the reliability of the questionnaire. The statistical analysis was done using descriptive statistics. Independent t-test and Chi-square test were also used to see whether pica practice is related to sociodemographic characteristics, dietary habits, and lifestyle factors. Results: Eight (4.7%) participants reported experiencing pica during pregnancy. Pica prevalence categorized by substances ingested as follows: ice cube (62.5%); dirt (12.5%); cigarette ash residue (12.5%); toothpaste (12.5%). Minority of women who practiced pica reported experiencing pica in previous pregnancy, and health problems-related to pica. Most women who practiced pica reported ingestion of pica item during the first trimester. Pica practice was significantly associated with smoking and psychological stress during pregnancy. Moreover, pica practice was related to the dietary intake of milk and fat. Conclusions: Pica practice is not common in the current sample. It was found that pica practice was associated with smoking and psychological stress. Health care professionals need to be conscious of the presence of this behavior. A nation-wide research of pica prevalence among pregnant women is highly needed. The phenomenon obviously needs further research. Funding Sources: The authors declare that no external financial support was received for this study.